Occurrence of contralateral breast cancer in a BRCA-positive breast cancer patient who underwent free TRAM flap reconstruction: a case report - Nonhyun Ha; Nakwon Choi; Yujin Myung; Chan Yeong Heo (Archives of Aesthetic Plastic Surgery)
This report presents a case of contralateral breast cancer in a BRCA mutation-positive patient who had previously undergone delayed free transverse rectus abdominis myocutaneous flap reconstruction for unilateral breast cancer. Having used up the available abdominal autologous tissue in the first reconstruction, a direct-to-implant procedure was employed for the reconstruction of the second, contralateral breast. Therefore, one breast was reconstructed using autologous tissue from the abdomen, while the other was asymmetrically reconstructed with an implant. If the risk of contralateral breast cancer had been anticipated initially, we might have opted for implant-based reconstruction from the start to facilitate a more symmetrical outcome in the event of subsequent contralateral reconstruction. This case underscores the importance of reviewing the risk of contralateral breast cancer in patients with unilateral breast cancer who also carry mutations in BRCA and other breast cancer susceptibility genes. Furthermore, it encourages consideration of how mutations in breast cancer susceptibility genes, including BRCA, influence the choice of plastic surgery reconstruction techniques. The findings from genetic testing for breast cancer susceptibility are now crucial to achieving aesthetic completeness in breast reconstruction.